Are there useful physiological or psychological markers for monitoring overload training in elite rowers? - Smith, T. B.; Hopkins, W. G.; Lowe, T. E. (International Journal of Sports Physiology and Performance, 2011)
There is a need for markers that would help determine when an athlete`s training load is either insufficient or excessive. In this study we examined the relationship between changes in performance and changes in physiological and psychological markers during and following a period of overload training in 10 female and 10 male elite rowers. Change in performance during a 4-wk overload was determined with a weekly 30-min time-trial on a rowing ergometer, whereas an incremental test provided change in lactate-threshold power between the beginning of the study and following a 1-wk taper after the overload. Various psychometric, steroid-hormone, muscle-damage, and inflammatory markers were assayed throughout the overload. Plots of change in performance versus the 4-wk change in each marker were examined for evidence of an inverted-U relationship that would characterize undertraining and excessive training. Linear modeling was also used to estimate the effect of changes in the marker on changes in performance. There was a suggestion of an inverted U only for performance in the incremental test versus some inflammatory markers, due to the relative underperformance of one rower. There were some clear linear relationships between changes in markers and changes in performance, but relationships were inconsistent within classes of markers. For some markers, changes considered to predict excessive training (eg, creatine kinase, several proinflammatory cytokines) had small to large positive linear relationships with performance. In conclusion, some of the markers investigated in this study may be useful for adjusting the training load in individual elite rowers.